Sale and Purchase Deed as Evidence in Resolving Land Sale and Purchase Default Disputes - Najma Syamila; Michellena Michellena; Salsabillah Ayu Puspita (Jurnal Indonesia Sosial Sains, 2024)
Indonesia as a country of law adheres to the Civil Law system where the source of Law and all rules applied in Indonesia must be based on what has been codified or written in the form of a law. The type of research used is qualitative research derived from legal materials. The research approach method used is laws and regulations and a case approach, with the method of collecting data from literature studies and data analysis using normative juridical analysis. It is divided into several legal orders, one of which we know, namely Civil Law. The problems handled in the Civil Law are individual persons, for example, the sale and purchase of land where two parties are involved in a civil bond. In buying and selling, there is a need for an agreement, then generally there is a Deed of Sale and Purchase (AJB) which is an authentic deed and plays an important role in the process of buying and selling land as a sign that there has been a legal act between the parties. However, in reality, there is still a default in the sale and purchase of land after the issuance of the AJB where the seller cannot fulfill the rights of the buyer as stated in the AJB. If a civil dispute cannot be resolved using mediation, it can be resolved by submitting it to the court. In the settlement of civil disputes in court, there is evidence where evidence must be submitted to strengthen the argument. In this case, the Deed of Sale and Purchase can be used as evidence that is classified as an authentic deed of evidence.